2018
DOI: 10.3892/mmr.2018.9249
|View full text |Cite
|
Sign up to set email alerts
|

Quercetin‑3‑O‑β‑D‑glucoside decreases the bioavailability of cyclosporin A through regulation of drug metabolizing enzymes, transporters and nuclear receptors in rats

Abstract: Quercetin is a flavonoid compound that is widely present in food and drink. Quercetin-3-O-β-D-glucoside (Q3GA) is a major metabolite of quercetin. The aim of the present study was to investigate the effect of Q3GA on the pharmacokinetics of orally and intravenously administered cyclosporin A (CsA) in rats, and to assess the effect of Q3GA on drug-metabolizing enzymes (DMEs), drug transporters (DTs) and nuclear receptors (NRs). The pharmacokinetic parameters of CsA were measured following oral (10 mg/kg) and in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 49 publications
1
8
0
Order By: Relevance
“…Quercetin and Q3GA exhibited similar inhibitory effects on the protein and mRNA expression levels of UGT1A1 in the small intestine and the liver. This is consistent with our preliminary data and previously published studies ( 19 , 43 ). It has also been reported that quercetin inhibits glucuronidation of ethanol in human liver microsomes and in recombinant UGT1A1, UGT1A3, UGT 1A4, UGT1A6 and UGT1A9 enzymes ( 44 ).…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…Quercetin and Q3GA exhibited similar inhibitory effects on the protein and mRNA expression levels of UGT1A1 in the small intestine and the liver. This is consistent with our preliminary data and previously published studies ( 19 , 43 ). It has also been reported that quercetin inhibits glucuronidation of ethanol in human liver microsomes and in recombinant UGT1A1, UGT1A3, UGT 1A4, UGT1A6 and UGT1A9 enzymes ( 44 ).…”
Section: Discussionsupporting
confidence: 94%
“…However, the underlying mechanisms for these interactions remain unclear. Our previous studies have demonstrated that Q3GA increases the C max , AUC 0-t and AUC 0-∞ of cyclosporine A (19,43). In order to further elucidate the underlying mechanisms of quercetin and Q3GA on the pharmacokinetics of cyclosporine A, the inhibitory effects of quercetin and Q3GA on the enzyme activity of recombinant UGT1A isoforms were investigated in vitro.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The method for the determination of CsA was based on our previous developed LC-MS/MS methods (Yang et al, 2018). The linear concentration range of CsA was 5-4000 ng/mL, and the lower limit of quantification was 5 ng/mL.…”
Section: Quantification Of Csamentioning
confidence: 99%
“…The 6‐h post‐LPS period was employed because it has been shown adequate for eliciting well‐defined signs of renal toxicity and inflammation 29‐31 . Further, the administration of immunosuppressants 2 h prior to LPS would allow a total of 8 h before the animal death, which is well within the reported half‐lives of these drugs when administered intravenously, thus maintaining therapeutically relevant blood concentrations of the drugs during the experimentation period 71‐73 . The collected serum was aspirated, divided into aliquots, and stored at −80℃ until used for the colorimetric measurement of creatinine and urea.…”
Section: Protocols and Experimental Groupsmentioning
confidence: 99%